Penggunaan Artificial Intelligence dan Dampaknya terhadap Kemampuan Berpikir Kritis Mahasiswa PPKn Universitas Mataram - Inni Khaerunnisa; Muhammad Mabrur Haslan; Ahmad Hudori (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
In todays’s digital era, rapid technological advancements, particularly the emergence of Artificial Intelligence (AI), have transformed how students access information and complete academic assignments. The growing reliance on AI in academic activities has raised concerns regarding its impact on students' critical thinking skills, specifically among students of Pancasila and Civic Education (PPKn) at the University of Mataram. This study aims to analyze student perceptions regarding AI usage and examine its impact on the critical thinking skills of PPKn students at the University of Mataram. The study employs a qualitative phenomenological approach. Data collection was conducted through semi-structured interviews—with subjects and informants selected via snowball sampling—as well as non-participant observation and document analysis. Data analysis involved data reduction, data presentation, and conclusion drawing. Meanwhile, data validity was verified through source, technique, and time triangulation. The results reveal three types of student perceptions: 1) A positive perception, viewing AI as a tool to accelerate data research and visualize concepts; 2) A negative perception, viewing AI as potentially creating challenges such as intellectual dependency that fosters mental laziness and the erosion of moral values; and 3) A shift in mindset, where AI aids in understanding and processing information but creates an illusion of independent thinking. Furthermore, AI has a dualistic impact on its users. Positive impacts include improved access to information, greater efficiency in literacy-related tasks, and the availability of additional information sources. Conversely, negative impacts include dependency on AI, diminished critical thinking skills, and threats to the originality of written work. The study concludes that AI elicits diverse perceptions and impacts regarding students' critical thinking skills, depending on how students utilize AI within their academic processes.